Regarding Treatment of Painful Diabetic Neuropathy With 10 kHz Spinal Cord Stimulation: Long-Term Improvements in Hemoglobin A1c, Weight, and Sleep Accompany Pain Relief for People With Type 2 Diabetes [Letter] - Zhou PB; Bao M; Sun HT (Journal of Pain Research)
Peng-Bo Zhou,1,2 Min Bao,3 Hong-Tao Sun1,2 1The First School of Clinical Medical, Lanzhou University, Lanzhou, Gansu, 730000, People’s Republic of China; 2Tianjin Key Laboratory of Neurotrauma Repair, Characteristic Medical Center of People’s Armed Police Forces, Tianjin, 300162, People’s Republic of China; 3Department of Neurosurgery, People’s Hospital of Liaoning Province, Shenyang, Liaoning, People’s Republic of ChinaCorrespondence: Hong-Tao Sun, Email sunhtlab@163.com; Min Bao, Email 13699250880@163.com